Design elements a graphic style manual : understanding the rules and knowing when to break them - Samara, Timothy (Page One, 2007)
"Design Elements is a fun and comprehensive manual for graphic designers that includes hundreds of tips and examples for designers to attain the fundamental skills that contribute to successful design. It is the most compact and lucid handbook available outlining the basic principles of layout, typography, color usage, space, image, and how to put it all together. Design Elements not only offers great tips on the basics, but also shows you how to break the rules without compromising communication or confusing your audience."--BOOK JACKET.